QTL analyses reveal clustered loci for accumulation of major provitamin A carotenes and lycopene in carrot roots - Santos, C.A.F.; Simon, P.W.
QTLs associated with products of the carotenoid pathway, including lycopene and the provitamin A carotenes a- and b-carotene, were investigated in two unrelated F2 carrot populations, derived from crosses between orange cultivated B493 and white wild QAL (Population 1), and orange cultivated Brasilia and darkorange cultivated HCM (Population 2). The mapping populations of 160 and 180 individuals, respectively, were analyzed with single-marker and interval-mapping statistical approaches, using coupling linkage maps for each parent. Single markers were selected for further analysis based on the Wilcoxon sum-rank non-parametric test. Interval mapping performed with Population 2 detected four, eight, three, one and five putative QTLs associated with accumulation of n-carotene, acarotene, b-carotene, lycopene and phytoene, respectively. Among these, the major QTLs explained 13.0
Keywords: BIOCHEMICAL PATHWAY; DAUCUS CAROTA L; LINKED PATHWAY GENES; WILCOXON SUM-RANK TEST